2013
DOI: 10.5812/archcid.16207
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of blaTEM, blaSHV and blaCTX-M Genes Among Escherichia coli Isolates Causing Urinary Tract Infection in Children

Abstract: Background: Emerging antibacterial resistance rates and extended-spectrum-β-lactamase producing Escherichia coli recovered from urinary tract infections (UTI) is an increasing problem in different regions, limiting therapeutic options. Objectives: The aim of this study was the detection of bla TEM , bla SHV and bla CTX-M genes among Escherichia coli strains causing Urinary Tract Infection in children from Iran. Materials and Methods: A total of 100 Escherichia coli isolates were collected from urine specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Several virulence determinants contribute to the pathogenicity of E. coli in UTI ( 17 , 19 , 27 ). They are the product of different genes, which can be detected by PCR method ( 9 , 22 ). However, there is always the possibility of mutation at the level of the corresponding gene, leading to the absence of its detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several virulence determinants contribute to the pathogenicity of E. coli in UTI ( 17 , 19 , 27 ). They are the product of different genes, which can be detected by PCR method ( 9 , 22 ). However, there is always the possibility of mutation at the level of the corresponding gene, leading to the absence of its detection.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred non-duplicate E. coli isolates were recovered by urine culture from 250 consecutive adult patients with community-acquired pyelonephritis or cystitis over a period ranging from April to September 2013 in Zabol, Iran. The isolation and identification of E. coli isolates were performed by standard bacteriological and biochemical tests using Gram staining, catalase test, indole, methyl red, Voges-Proskauer test, nitrate reduction, urease production, Simmons citrate agar, and various sugar fermentation tests ( 20 - 22 ). The bacteria were maintained in Tryptic Soy Broth (TSB) (Sigma; The USA) with Glycerol at -70°C.…”
Section: Methodsmentioning
confidence: 99%
“…Feizabadi et al in Iran showed that 46.51% ( n = 40) of K. pneumoniae isolates were bla CTX-M positive [ 24 ]. Also, Goudarzi et al reported that 74 (74%) of Escherichia coli isolates were bla CTX-M-15 positive [ 25 ]. Reports of OXA-48-producing Enterobacteriaceae have recently dramatically increased worldwide, particularly in the Middle East and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, multidrug-resistant Gram-negative rods will be a serious problem if no adequate action is taken (4,5). Unfortunately, the issue of antibiotic resistant bacteria in Iran is increasing, following the rising trend of its global counterpart (6). One of the most common reasons for this trend is represented by the widespread overuse and incorrect prescribing practices.…”
Section: Contextmentioning
confidence: 99%